An analysis of unofficial sanction of India from neo-colonialism perspective - Pant, Bhuwaneswor (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
This paper mainly analyses the unofficial sanction of India against Nepal from neocolonial perspectives. The paper argues that the sanction of India against Nepal has-been the repercussion of colonial hangover of the former. India saw new constitution of Nepal through latter’s inferiority to write democratic constitution. India as a postcolonial nation inherited the colonial culture from British rule. It has been almost seven decades that India got independence from British rule but in reality it couldn’t escape from the colonial culture left by the British. The study has been conducted as library research reviewing the wide range of research, articles and reports. The study is qualitative in nature, which has incorporated the description, assessment, examine and comparative methods.